Quest : questions & answers on the euro and european economic and monetary union - European Commission; European Commission (Brussels : European Commission, 1998)
Questions and answers on euro as the new currency for Europe
Photocopied and spiral-bound.
rua 25/11/16
Loans
Keywords: Money; Monetary policy; Euro; Monetary unions; International economic integration; Europe - European Union Countries